Improving Branding through Product Packaging - Pertiwi, Meilani Intan; Wahyuningrum, Indah Fajarini Sri; Agustina, Linda; Aji, Tri Susilo Wahyu (Universitas Negeri Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Kalisalak Village, Batang Regency, have great potential in producing local products such as gethuk, jenang, dodol, herbal drinks, and tea. However, most products still face challenges in branding and packaging, including the absence of labels, barcodes, and legal certification, as well as simple and unattractive packaging that reduces market competitiveness. This community service program aimed to enhance the knowledge, skills, and awareness of MSME actors regarding the importance of branding through product packaging that is appealing, informative, and meets industrial standards. The program involved 30 participants, including MSME owners and residents interested in starting new businesses. The team designed the activities using participatory methods, conducting seminars, practical training, group discussions, mentoring, and gamification to strengthen participants' engagement and understanding. The team implemented the process in three stages: preparation, execution, and evaluation, and used pretest and posttest instruments to support the evaluation. The results indicated a significant improvement in participants' knowledge and skills, with most participants producing improved packaging designs and showing commitment to applying them to their products. Overall, the program effectively addressed partners' needs and strengthened the competitiveness of local MSME products in broader markets.